Nursing care for the transsexual population in primary care - Silva, Ana Karoline Farias da (2024)
to analyze the evidence in the literature on nursing care for thetranssexual population in primary care. Method: Integrative literature review,carried out in the Virtual Health Library, Latin American and Caribbean Literaturein Health Sciences (LILACS) and Online Scientific Electronic Library (SCIELO)databases, using the descriptors Nursing care AND Transgender people ANDPrimary Care Nursing. Results: Found 2 articles, published in the last 5 years. It wasevidenced important gaps that come from the academic formation, in theunpreparedness and lack of knowledge about sexuality. Conclusion: It is concluded,therefore, that few articles were found with this theme, highlighting the need to carryout more research on the topic of nursing care for the transsexual population.